1992
DOI: 10.3758/bf03212239
|View full text |Cite
|
Sign up to set email alerts
|

Visual parsing and response competition: The effect of grouping factors

Abstract: When the task is to categorize a target letter at a known location, subjects show more interference from incongruent distractors that are relatively close (E. A. Eriksen & C. W. Eriksen, 1974) or that share common motion with the target (Driver & Baylis, 1989). In eight experiments, we examined whether static factors other than proximity can affect the amount of interference. When distractors and the target letter were in the same color, the distractors interfered more than they did when they were in a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
285
5
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(320 citation statements)
references
References 35 publications
29
285
5
1
Order By: Relevance
“…Indeed, they appear to be in direct opposition to the position some of us had adopted in the past. Whereas Baylis and Driver (1992) argued that ªvisual attention is directed to groups derived from a preattentive segmentation of the scene according to Gestalt principlesº, in the same year Mack et al (1992, p. 498) concluded that ªno perception of either texture segregation of Gestalt groupingº takes place for unattended stimuli! 5.…”
Section: Attention and Image Segmentationmentioning
confidence: 99%
“…Indeed, they appear to be in direct opposition to the position some of us had adopted in the past. Whereas Baylis and Driver (1992) argued that ªvisual attention is directed to groups derived from a preattentive segmentation of the scene according to Gestalt principlesº, in the same year Mack et al (1992, p. 498) concluded that ªno perception of either texture segregation of Gestalt groupingº takes place for unattended stimuli! 5.…”
Section: Attention and Image Segmentationmentioning
confidence: 99%
“…While many researchers would agree that location is an important defining characteristic of an object, most would argue that it is not the only one. Grouping by similarity (Baylis & Driver, 1992), common fate (Driver & Baylis, 1989), and connectedness (Kramer & Jacobson, 1991 ) have been shown to produce strong object-based effects independent of proximity. It may be possible to incorporate the effects of grouping by similarity and common fate into CTVA (see below), but connectedness may be difficult because it implies a hierarchical structure that is not captured in CODE's idealization of objects as points (see Palmer & Rock, 1994).…”
Section: Limitations Of Ctvamentioning
confidence: 99%
“…An important direction for future research is to extend CODE and CTVA to deal with other grouping principles. Grouping by similarity is a good candidate for the first step in that direction because it is well studied perceptually (e.g., Beck, Prazdny, & Rosenfeld, 1983;Bergen, 1991 ) and it has powerful effects on attention (e.g., Baylis & Driver, 1992;Duncan & Humphreys, 1989;Harms & Bundesen, 1983;Humphreys & Miiller, 1993;Ivry & Prinzmetal, 1991;Wolfe, 1994). The mechanisms for dealing with similarity effects may already be present in CTVA.…”
Section: Proximity and Grouping Effects In Partial Report Several In-mentioning
confidence: 99%
“…For example, Posner (see Footnote 3 in Duncan, 1984 ) has suggested that if an attentional spotlight were to operate in three-dimensional (3-D) rather than two-dimensional (2-D) space, the overlapping box and line might be separable in depth and then attention may select one of the objects spatially in depth. A second concern is that Duncan's results may reflect a difficulty in attending to different spatial frequencies rather than to different objects; whereas the two attributes of the line (texture and line orientation) are primarily available at high spatial frequencies and the two attributes of the box (height and gap) are available primarily at low spatial frequencies, the attributes of the box and of the line might be segregated not by object-based attention per se but by setting a spatial frequency filter at different levels of coarseness (see Baylis & Driver, 1992Lavie & Driver, 1996 ;and Watt, 1988 , for further discussion).Recent researchers have circumvented these potential shortcomings and have shown that the features of a single object can indeed be preferentially selected and processed. For example, in Lavie and Driver's (1996) study, participants judged whether two odd elements (e.g., two dots or a dot vs. a gap) in a display of two crossed dashed lines were the same or different.…”
mentioning
confidence: 99%